Using Sina-Weibo microblogs to inform the development and dissemination of health awareness material about Zika virus transmission, China, 2016–17 - Hou, Qian; Zhao, Yueqiao; Su, Xiaoge; Rong, Rong; Situ, Sujian; Cui, Ying (PLOS ONE, 2022)
Background On 1 February 2016, the World Health Organization declared Zika transmission a public health emergency of international concern. Monitoring and responding to community awareness, concern, and possible knowledge gaps are critical during public health emergencies. Here, we describe the review and analysis of micro-blogs posted on Sina-Weibo, China’s largest social media platform, to develop and disseminate a Zika virus education campaign. Methods We used CYYUN Voice Express’ Weibo Spider tool and the search terms of "Zhaika" OR "Zika" OR "Zikv” to capture microblogs about Zika virus retrospectively from February 1 to December 31, 2016 and prospectively from June 1 to November 15, 2017. We described microblogs meeting our inclusion criteria by month and Zika virus outbreaks in Asia and by source (e.g., government agency, individual, or other). We identified common misleading or inaccurate content authored by individual micro-bloggers (i.e., not supported by available scientific evidence) through a qualitative review. We used this information to develop and disseminate health awareness material about the Zika virus through China CDC’s 12320 Health Hotline Weibo account. An online survey was conducted to obtain feedback on the material. Results We captured 15,888 microblogs meeting our inclusion criteria. Zika-related microblogs peaked in September 2016, corresponding to news reports about the Zika outbreak in Singapore (August to November 2016). Most microblogs (12,994 [82%]) were authored by individual users, followed by media agencies (842 [5%]), businesses (829 [5%]), international organizations (370 [2%]), and Chinese government agencies (235 [1%]). Relevant microblogs primarily focused on clinical symptoms and health risks, modes of transmission, and actions taken by individuals to prevent infection and seek health care. Incorrect and/or mis-leading information from individual users concentrated on modes of transmission and possible treatments. The microblog "#Zika is that far and this close" health campaign was posted on Sina-Weibo and Baidu (Internet search engine in China) on September 18, 2016. Younger respondents (p-value = 0.01), and those with at least a college education (p-value = 0.03), were more likely than other respondents to consider the online campaign reliable and trustworthy. Conclusion Routine review of Sina-Weibo and other social media platforms could enhance the ability of public health staff to effectively respond to community concerns and awareness during public health emergencies. Advancements of social media monitoring tools and staff training could help to promote health awareness during emergencies by directly addressing public perceptions and concerns. Various approaches may be needed to reach different at-risk populations, particularly older and less educated populations who may prefer more traditional modes of communication.